Altered neural recruitment during single and dual tasks in athletes with repeat concussion - Hagen, Andrew C.; Tracy, Brian L.; Stephens, Jaclyn A. (Frontiers in Human Neuroscience, 2024)
Sports-related concussions (SRCs) pose significant challenges to college-aged athletes, eliciting both immediate symptoms and subacute cognitive and motor function impairment. While most symptoms and impairments resolve within weeks, athletes with repeat SRCs may experience heightened risk for prolonged recovery trajectories, future musculoskeletal injuries, and long-term neurocognitive deficits. This study aimed to investigate the impact of repeat SRCs on dual task performance and associated neural recruitment using functional near-infrared spectroscopy (fNIRS). A total of 37 college-aged athletes (ages 18–24) participated in this cross-sectional observational study, 20 with a history of two or more SRCs, and 17 controls that had never sustained an SRC. Participants completed the Neuroimaging-Compatible Dual Task Screen (NC-DTS) while neural recruitment in the frontoparietal attention network and the primary motor and sensory cortices was measured using fNIRS. Athletes with repeat SRCs exhibited comparable single task and dual task performance to control athletes. Neuroimaging results indicated altered neural recruitment patterns in athletes with repeat SRCs during both single and dual tasks. Specifically, athletes with repeat SRCs demonstrated increased prefrontal cortex (PFC) activation during single motor tasks compared to controls (p < 0.001, d = 0.47). Conversely, during dual tasks, these same athletes exhibited reduced PFC activation (p < 0.001, d = 0.29) compared to their single task activation. These findings emphasize that while athletes with repeat SRCs demonstrate typical single and dual task performance, persistent alterations in neural recruitment patterns suggest ongoing neurophysiological changes, possibly indicating compensatory neural strategies and inefficient neural resource allocation, even beyond symptom resolution and medical clearance.